(untitled) (Global Journal of Management and Business Research, 2011)
This paper aims to investigate the impact of variables (career development, supervisor support, work environment, work life balance) on employee retention.A total of 50 interviews were taken from managers of different BPO organizations in Pakistan. Graphical Analysis is indicating that these variables have significant and positive impact on employee retention. Very less research have been done about employee retention in business process out sourcing, especially in Pakistan. So, these finding will provide some insights to BPO#x2019;s managers to make policies about employee retention in Pakistan.